SKILLS OF USING GOOGLE BARD FOR MONITORING STUDENT SKILLS - Fayzieva Nigora Nurmukhammedovna (Bright Mind Publishing, 2025)
This article explores how educators can leverage Google Bard, an AI-powered conversational tool, to monitor and enhance students' skills. By utilizing Bard’s capabilities to assess student understanding, generate personalized assessments, and provide real-time feedback, teachers can track progress, identify learning gaps, and offer targeted interventions. The article highlights the benefits of using Bard for efficient skill monitoring, such as immediate feedback and data-driven insights, while also addressing potential challenges related to privacy, over-reliance on AI, and access issues. Ultimately, the integration of Google Bard into the classroom offers an innovative way to personalize learning and improve educational outcomes.
Keywords: Google Bard, AI in education, personalized learning, real-time feedback, assessment tools, progress tracking, collaborative learning, educational technology, conversational AI, learning outcomes, adaptive learning, EdTech, Student performance.